Clinical Efficiency of Diode Lasers (810+980nm) in Exposure of Maxillary Impacted Canines - Alaa Faiz Abdullah Alashbal; Balsam Saadi Abdul Hameed; Soudad Salman Ahmed (University Library System, University of Pittsburgh, 2024)
Objective: An impacted canine has no eruption following the completion of the normal growth pattern. To expose an impacted canine, a laser can be used as an additional tool in addition to a scalpel and electrocautery. To compare the effectiveness of a dual diode laser with a traditional scalpel procedure for exposing impacted canines, with the parameters of bleeding and pain as main outcomes. Methods: Thirty patients were chosen for this investigation. Each of them needed an operation for canine impaction, and they were divided into two groups at random: the study group, which were treated with a dual diode laser (980+810nm), and included fifteen patients, and the control group, which were treated with a scalpel. Data obtained prior to, during, and following surgery were compared. There were follow-ups after two hours, on the second, and third days after surgery. The Student's t and the one-way ANOVA tests were used for all comparisons. Results: Thirteen males and seventeen females were examined in this study, and their mean age was 23 years. Intraoperative bleeding score showed a significantly decrease in laser group versus the surgical blade group (0.4666 vs. 0.29333, P=0.001). The postoperative pain score was significantly decreased in the laser group compared to the surgical blade group, at two hours (4.6 vs 8.233, P = 0.001), two days (2.067 vs 4.833, P=0.001), and three days (1.066 vs 2.01, P=0.001). There were significant differences in the pain and bleeding scores (P≤ 0.05). Conclusion: When using a dual diode laser (810+910nm) as opposed to a scalpel, hemostasis can be achieved with minimal pain.